2019
DOI: 10.3390/en12224363
|View full text |Cite
|
Sign up to set email alerts
|

Active Disturbance Rejection Control Scheme for Reducing Mutual Current and Harmonics in Multi-Parallel Grid-Connected Inverters

Abstract: With the increasing penetration of renewable energy sources into modern power systems, parallel inverters with LCL filters are commonly employed in the grid interface, giving rise to potential resonance problems. Among the different resonances, interactive resonance is triggered by interaction among inverters when different current references are applied to parallel inverters. It may also feature a mutual current that circulates among inverters instead of flowing into the grid and introduces harmonics or insta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…(29) (30) From equation 9, the rotor flux is given by: (31) (32) From the previous equations, the stator voltages can be given by the following expressions: We can so present a DFIG control block by ADRC adapted in the voltage dip event (figure 7): The proposed method, which consists in taking into account the dynamics of the stator flux during a voltage dip, can be further improved by using an LCL filter instead of an L filter. Indeed, the results presented by the authors in [11][12][13] show that this higher order filter allows a better attenuation and reduction of the current harmonics absorbed by the power converters.…”
Section: Control Strategy Of Dfig During a Voltage Dipmentioning
confidence: 99%
See 1 more Smart Citation
“…(29) (30) From equation 9, the rotor flux is given by: (31) (32) From the previous equations, the stator voltages can be given by the following expressions: We can so present a DFIG control block by ADRC adapted in the voltage dip event (figure 7): The proposed method, which consists in taking into account the dynamics of the stator flux during a voltage dip, can be further improved by using an LCL filter instead of an L filter. Indeed, the results presented by the authors in [11][12][13] show that this higher order filter allows a better attenuation and reduction of the current harmonics absorbed by the power converters.…”
Section: Control Strategy Of Dfig During a Voltage Dipmentioning
confidence: 99%
“…In [12] and [13], the work is focused on the use of an LCL filter and the problem of interactive resonance which is triggered by the interaction between inverters, this causes a mutual current in the grid. For this disturbance, considered as external, the authors propose a control approach to estimate and then cancel these disturbances by using ADRC technique [12]. This technique is introduced first for an L filter and then for an LCL.…”
Section: Introductionmentioning
confidence: 99%
“…Owing to galvanic isolation necessity, high-frequency transformer (HFT)-based inverters have been developed for inverter footprint and efficiency improvement [14,15]. HFT-based inverters start with a two-stage operation using a decoupling capacitor/inductor, which increases the required components number, size, and system overall footprint [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Not respecting this requirement leads to crosscurrent or circulating current between the inverters with the effect of reducing power efficiency and system reliability. The circulating current behavior in multiparallel connected inverters has been widely discussed in [24][25][26][27]. In [24], the authors studied the effect of this current in a system with two inverters and in a more general case of N inverters.…”
Section: Introductionmentioning
confidence: 99%
“…The authors also concluded that the circulating current is independent of the load, that is, a current superimposed on the normal current and, finally, that can cause power exchange among the inverters connected (in the case of a no load or low-load condition). In [25], an active rejection control based on a Reduced-order Extended State Observer (RESO) is reported. The scheme proposed reduces the mutual currents with a less model-dependent control design.…”
Section: Introductionmentioning
confidence: 99%